Palmitoylethanolamide Counteracts Enteric Inflammation and Bowel Motor Dysfunctions in a Mouse Model of Alzheimer’s Disease - D’Antongiovanni, Vanessa; Pellegrini, Carolina; Antonioli, Luca; Benvenuti, Laura; Di Salvo, Clelia; Flori, Lorenzo; Piccarducci, Rebecca; Daniele, Simona; Martelli, Alma; Calderone, Vincenzo; Martini, Claudia; Fornai, Matteo (Frontiers in Pharmacology, 2021)
Palmitoylethanolamide (PEA), an endogenous lipid mediator, is emerging as a promising pharmacological agent in multiple neurodegenerative disorders for its anti-inflammatory and neuroprotective properties. However, its effects on enteric inflammation and colonic dysmotility associated with Alzheimer’s disease (AD) are lacking. This study was designed to investigate the beneficial effect of PEA administration in counteracting the enteric inflammation and relieving the bowel motor dysfunctions in an AD mouse model, SAMP8 mice. In addition, the ability of PEA in modulating the activation of enteric glial cells (EGCs), pivotally involved in the pathophysiology of bowel dysfunctions associated with inflammatory conditions, has also been examined. SAMP8 mice at 4 months of age were treated orally with PEA (5 mg/kg/day) for 2 months. SAMR1 animals were employed as controls. At the end of treatment, parameters dealing with colonic motility, inflammation, barrier integrity and AD protein accumulation were evaluated. The effect of PEA on EGCs was tested in cultured cells treated with lipopolysaccharide (LPS) plus β-amyloid 1–42 (Aβ). SAMP8 treated with PEA displayed: 1) an improvement of in vitro colonic motor activity, citrate synthase activity and intestinal epithelial barrier integrity and 2) a decrease in colonic Aβ and α-synuclein (α-syn) accumulation, S100-β expression as well as enteric IL-1β and circulating LPS levels, as compared with untreated SAMP8 mice. In EGCs, treatment with PEA counteracted the increment of S100-β, TLR-4, NF-κB p65 and IL-1β release induced by LPS and Aβ. These results suggest that PEA, under a condition of cognitive decline, prevents the enteric glial hyperactivation, reduces AD protein accumulation and counteracts the onset and progression of colonic inflammatory condition, as well as relieves intestinal motor dysfunctions and improves the intestinal epithelial barrier integrity. Therefore, PEA represents a viable approach for the management of the enteric inflammation and motor contractile abnormalities associated with AD.